Synthesis and characterization of tough foldable and transparent poly(styrene-co-butyl acrylate)/nanoporous cellulose gel (NCG) nanocomposites - J. S. Borah; D. S. Kim (eXPRESS Polymer Letters, 2017)
Poly (styrene-co-butyl acrylate)/nanoporous cellulose gel nanocomposites [P (St/BA)/NCG] were synthesized by in-situ polymerization of styrene/butyl acrylate (St/BA) monomer mixtures in nanoporous regenerated cellulose gels. The three-dimensional nanoporous cellulose gels (NCGs) were fabricated via dissolution and coagulation of cellulose from aqueous sodium hydroxide (NaOH)/urea solution. The NCG contents in nanocomposites were controlled between 16 and 44% v/v by changing water content of starting hydrogels via compression dewatering. Scanning electron microscopy (SEM) analysis showed that the interconnected nanofibrillar network structure of NCGs was preserved well in the nanocomposites after insitu polymerization. The resulting nanocomposites exhibited excellent transparency (up to 82%) in the visible region and high mechanical strength, with a tensile strength of up to 56.0 MPa, Young’s modulus of up to 2195 MPa and elongation at break up to 80.9%. Dynamic mechanical analysis (DMA) showed a remarkable improvement (by over 3 orders of magnitude) in tensile storage modulus above glass transition temperature of the copolymer. The nanocomposites also showed significant improvements in thermal stability as well as water resistance over NCG.